2018
DOI: 10.1186/s12886-018-0950-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity improvement after phacoemulsification cataract surgery in patients aged ≥90 years

Abstract: BackgroundVisual acuity (VA) outcomes after phacoemulsification cataract surgery in the very elderly (≥90 years) compared to those in younger patients remain unclear till date.MethodsWe retrospectively investigated 138 (group 1) and 152 (group 2) eyes in patients aged ≥90 and < 80 years, respectively, with senile cataracts who underwent phacoemulsification and intraocular lens implantation between 2014 and 2016. Four highly experienced ophthalmic surgeons performed the procedures. Intra- and post-operative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…After surgery, we found a significant improvement in visual acuity, refraction and quality of life (in all CATQUEST-9SF dimensions), with a low proportion of intraoperative or postoperative complications. These results corroborate that also in an oncology population, cataract surgery is highly effective, leading to improved vision and quality of life [ 14 , 28 ]. However, until ICHOM standard set to release, there was no validated tool available, to characterize a specific population such as assessed at IPO-Porto.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…After surgery, we found a significant improvement in visual acuity, refraction and quality of life (in all CATQUEST-9SF dimensions), with a low proportion of intraoperative or postoperative complications. These results corroborate that also in an oncology population, cataract surgery is highly effective, leading to improved vision and quality of life [ 14 , 28 ]. However, until ICHOM standard set to release, there was no validated tool available, to characterize a specific population such as assessed at IPO-Porto.…”
Section: Discussionsupporting
confidence: 84%
“…It is estimated that it allows people to increase their economic productivity by up to 1500% of the cost of surgery during the first postoperative year [ 8 ]. Additionally, several studies have shown that cataract surgery is associated with improvement of visual function and psycho social health status [ 13 , 14 ], reduction of falls [ 15 , 16 ], lower prevalence of hip fractures [ 17 ], and improvement in quality of life (e.g. social and emotional aspects) [ 13 , 18 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, this rate was found to be 6.6%. This rate was found to be higher than that of Goyal et al (34), Özer et al (35), Neff et al (37), and Tzamalis et al (38) Increased visual acuity after cataract surgery has been shown in many studies (39)(40)(41). In our study, the postoperative visual acuity level was found to be significantly increased compared to the preoperative visual acuity level.…”
Section: Discussionmentioning
confidence: 66%
“…No significant difference was observed in the CDVA between groups at the 4week follow-up after resolution of postoperative corneal oedema in all cases in both groups. This reflects the equivalent safety of both techniques in avoiding major vision-threatening complications during the management of hard cataracts, thereby attaining expected CDVA improvement (Artzen et al 2009;Haripriya et al 2012;Toyama et al 2018).…”
Section: Discussionmentioning
confidence: 98%